1969
DOI: 10.1111/j.1476-5381.1969.tb08301.x
|View full text |Cite
|
Sign up to set email alerts
|

The cardio‐toxicity of isoprenaline during hypoxia

Abstract: The effects of the intravenous injection of isoprenaline on heart rate and arterial pressure has been studied in dogs artificially respired with room air or with 12% oxygen—88% nitrogen. In dogs breathing room air, isoprenaline in doses from 0.02 to 500 μg/kg increased heart rate and reduced arterial pressure. Ventricular fibrillation was produced in one out of three dogs given 250 μg/kg. This was the only dog breathing room air which was killed by isoprenaline. In dogs breathing room air the repeated intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…The second group of possible mechanisms relates to the overuse of beta agonists in the situation of a life-threatening attack of asthma, in which the cardiac side effects are likely to be particularly harmful in the presence of severe hypoxia (1-3). In particular, Collins et al (13) showed that it was possible to administer large doses of isoprenaline intravenously to anaesthetized dogs with normal blood gas tensions without producing serious arrhythmias, whereas much smaller doses caused fatal cardiac depression during hypoxemia. The response involved asystolic arrest and was the same as that observed with more severe hypoxemia alone.…”
Section: Mechanismsmentioning
confidence: 99%
“…The second group of possible mechanisms relates to the overuse of beta agonists in the situation of a life-threatening attack of asthma, in which the cardiac side effects are likely to be particularly harmful in the presence of severe hypoxia (1-3). In particular, Collins et al (13) showed that it was possible to administer large doses of isoprenaline intravenously to anaesthetized dogs with normal blood gas tensions without producing serious arrhythmias, whereas much smaller doses caused fatal cardiac depression during hypoxemia. The response involved asystolic arrest and was the same as that observed with more severe hypoxemia alone.…”
Section: Mechanismsmentioning
confidence: 99%
“…Death was produced in a similar way in animals with hypoxaemia by giving four or five doses of isoprenaline (2·5 ìg/kg) at five minutes intervals or by two doses of 25 ìg/kg. The final reduction in arterial pressure during a fatal response resulted from a reduction in cardiac contractility 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The electrocardiogram showed that, in most cases, sinus rhythm persisted even after the arterial pressure had fallen, though occasionally a slow A-V nodal rhythm or irregular ventricular ectopic beats occurred. It has previously been shown that within seconds of the fatal dose, there was a sharp decrease in cardiac output and stroke volume, accompanied by increases in ventricular end-diastolic pressures, indicating a failure of myocardial contractility (Collins et al, 1969;Swanton, 1972). The terminal response developed suddenly: cardiac output, stroke volume, and right and left ventricular responses to the penultimate dose have been shown to be relatively normal, though there was some reduction in heart rate and arterial pressure responses with repeated doses of isoprenaline.…”
Section: Infusionmentioning
confidence: 99%
“…In an earlier study, Collins, McDevitt, Shanks & Swanton (1969) described cardiotoxic effects from the administration of intravenous isoprenaline to hypoxic dogs, often resulting in their death. It was found that dogs breathing room air could withstand the administration of repeated small doses or single large doses of isoprenaline (up to 500 pg/kg) with no ill effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation